Unlocking the Needs to Design Audiovisual Media to Incorporate Climate Change Education in ELT - Maskana, Nurul; Silvhiany, Sary; Mirizon, Soni (UNIB Press, 2024)
Climate change is a crucial topic to be included in the Grade 7 Junior High English book, highlighting its significance in educating students about the causes, impacts, and potential solutions to this global issue. This study focuses on conducting a need analysis related to the use of audiovisuals in learning climate change within the context of EFL classrooms as needs analysis will inform us what is suitable for 7th grade students who have just started learning English formally. Specifically, the research investigates the requirements of 7th-grade students at MTs Negeri 2 Palembang for audiovisual resources to enhance climate literacy. Employing a mixed-method approach, combining quantitative and qualitative data collection methods such as questionnaires and interviews, the study uncovers students' strong desire to learn about climate change through audiovisuals. Moreover, it identifies a preference for audiovisual media over traditional text-based materials and highlights the support from teachers and stakeholders at MTs Negeri 2 Palembang for integrating climate change education into EFL teaching practices. In light of these findings, the researchers recommend the development of audiovisual resources tailored to facilitate the seamless integration of climate change education within EFL classrooms. Additionally, they advocate for teacher training to effectively utilize audiovisual media as an instructional tool. This study contributes significantly to climate change education by addressing the identified needs of both students and teachers, thereby guiding the design of effective instructional materials and teaching practices.